Estudio de la coordinación de las protecciones por métodos computarizados aplicados al centro comercial policentro - Cando, Geovanny (2010)
study addresses an important field in the design of an electrical system either commercial or industrial, this is the coordination of electrical protection. The coordination of the protection depends on the good or electrical system mal function. This study involves coordination of the protections from Main Substation (69/13.2 KV ) to the load bars 440V and 220V. A level of 69kV and up to the main bar to 13.2 KV the protection is done via the electronic relays digitrip Westinghouse type. The lines of 13.2KV are protected with electronic relays and fuses INEPAR in most cases, as will be seen later. The bars at 440V and 220V are protected by the Geneal.Electric Adjustable Breakers.